Al-Taujīh al-Tahwī fi Takhrījī Ba’ḍu al-Masā’īla al-Fiqhiyya - Ali Abubakar Basalamah (Al-Jami'ah Research Centre, 1996)
No one disagrees on the role of Arabic grammar in determining of text, included the reiigious one so any Islamic Scholar cannot forget it in deducting legal classifications and ritualistic rule in this article, the writer brings six examples within which he demonstrates how grammatical arguments have been used to argue for or against such ritual or legal opinion. For instance, it is stated in the koran, al-Anām. 6:145, that among the prohibited food is “the fresh of swine for it is unclean’” the question is whether it is only the flesh which is unclean or all parts of the swine. For (in the Arabic text) the pronoun ‘it’ can refer either to the flesh or to the swine. One can argue for the uncleanness of all parts of the body of swine. Saying that pronoun must be referred to the closest precedent, but against it one can say that of the swine is a determiner of the flesh. The examples given in this article are taken from chapters of fiqh dealing with purification, prayer, pilgrimage, judgement, testament, and endowment. It is beyond any dout that the contribution of naḥu to the solving of each problem is great although not always decisive. [Kaitan nahw'u dengan pengertian nas-nas (dalam hal yang berhubungan dengan Islam selalu berupa teks berbahasa Arab) sedemikian erat, sehingga orang tidak dapat mengabaikannya dalam usaha untuk mendeduksikan sesuatu hukum dari nas-nas itu. Dalam tulisan ini diberikan beberapa contoh perdebatan beberapa ahli dalam 'Memenangkan' pendapat kefiqihan tertentu yang di dalamnya nahwu muncul sebagai senjata yang tak terbantah. Misalnya, dalam Al-Qur'an, Al-An'ām, 6:145, dinyatakan bahwa makanan yang diharamkan antara lain adalah